Pengaruh Penerapan Model Pembelajaran Metakognitif terhadap Kemandirian Belajar dan Kemampuan Berpikir Kreatif Siswa - Arsyad, Nurdin; Djam'an, Nurwati; Firda Amelia (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Self-directed learning and creative thinking are essential 21st-century skills that need to be optimally developed in mathematics education. This study aimed to investigate how the implementation of a metacognitive learning model influences students’ self-directed learning and creative thinking skills. A quasi-experimental design was employed involving ninth-grade students at SMP Telkom Makassar. The population comprised all ninth-grade students, with data collected using a self-directed learning questionnaire and a creative thinking skills test. In the experimental class, the mean self-directed learning score after the treatment was 3.59 with an average normalized gain of 0.48, and 100% of students achieved at least a moderate category. The mean creative thinking score reached 83.86 with an average gain of 0.77, and 90.3% of students exceeded the minimum mastery criterion. In contrast, the control class obtained a mean self-directed learning score of 3.39 with an average gain of 0.39, and 96.7% of students reached at least a moderate category. The mean creative thinking score in this class was 72.50 with an average gain of 0.61, and 56.7% of students surpassed the minimum mastery criterion. Inferential statistical analysis revealed that the metacognitive learning model had a significant effect on students’ self-directed learning and creative thinking. These findings underscore the importance of process-oriented mathematics instruction that emphasizes self-regulation and creativity. Therefore, metacognitive learning is recommended as an effective instructional strategy to enhance students’ learning independence and creative thinking skills.